Lanthanide MOFs for inducing molecular chirality of achiral stilbazolium with strong circularly polarized luminescence and efficient energy transfer for color tuning - Zeng, Min (Chem Sci, 2020)
We present herein an innovative host–guest method to achieve induced molecular chirality from an achiral stilbazolium dye (DSM). The host–guest system is exquisitely designed by encapsulating the dye molecule in the molecule-sized chiral channel of homochiral lanthanide metal–organic frameworks (P-(+)/M-(−)-TbBTC), in which the P- or M-configuration of the dye is unidirectionally generated via a spatial confinement effect of the MOF and solidified by the dangling water molecules in the channel. Induced chirality of DSM is characterized by solid-state circularly polarized luminescence (CPL) and micro-area polarized emission of DSM@TbTBC, both excited with 514 nm light. A luminescence dissymmetry factor of 10(−3) is obtained and the photoluminescence quantum yield (PLQY) of the encapsulated DSM in DSM@TbTBC is ∼10%, which is close to the PLQY value of DSM in dilute dichloromethane. Color-tuning from green to red is achieved, owing to efficient energy transfer (up to 56%) from Ln(3+) to the dye. Therefore, this study for the first time exhibits an elegant host–guest system that shows induced strong CPL emission and enables efficient energy transfer from the host chiral Ln-MOF to the achiral guest DSM with the emission color tuned from green to red.